2004
DOI: 10.1007/s00330-004-2303-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of paramedian thalamic infarcts: MR imaging, clinical features and prognosis

Abstract: Considering the highly variable vascular supply of the thalamic nuclei, MRI and clinical syndromes can be heterogeneous in ischemic diseases. We attempt to determine MRI pattern and to analyse neurological features and prognosis of paramedian infarcts. In a prospective case series within 5 years from 1999 to 2003, MRI, MRA and clinical symptoms of 38 consecutive patients were analysed. The inferomedial (posterior thalamoperforating artery) territory was affected in 89%, and lesions in the anterolateral (tubero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
4
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 46 publications
1
48
4
4
Order By: Relevance
“…4,9,19,24,25 The AOP is rarely visualized with conventional angiography, and to our knowledge, only 3 other authors have successfully demonstrated this variant. 18,26,27 We were able to capture a striking image of the AOP with conventional angiography in 1 of our patients (Fig 6). Several clinical stroke patterns potentially involving the AOP have been described, including bilateral paramedian thalamic, 5,10,15 paramedian and polar thalamic, 16 and paramedian thalamic and mesencephalic.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…4,9,19,24,25 The AOP is rarely visualized with conventional angiography, and to our knowledge, only 3 other authors have successfully demonstrated this variant. 18,26,27 We were able to capture a striking image of the AOP with conventional angiography in 1 of our patients (Fig 6). Several clinical stroke patterns potentially involving the AOP have been described, including bilateral paramedian thalamic, 5,10,15 paramedian and polar thalamic, 16 and paramedian thalamic and mesencephalic.…”
Section: Discussionmentioning
confidence: 83%
“…1,2,6,[9][10][11][12][13] Many authors have demonstrated that the paramedian arteries can supply both the paramedian and the anterior thalamic territories, especially when the polar artery is absent. 1,4,6,9,10,[14][15][16][17][18][19] The variable presence of the polar artery (absent in 30%-60% of the population) 7,15,16 is not surprising because it arises from the PcomA, which itself is highly variable and can be absent or hypoplastic. One case series reported 7 of 8 bilateral paramedian thalamic infarcts extended into the anterior thalamic territory of the polar artery.…”
mentioning
confidence: 99%
“…Furthermore, the anterior choroidal artery (AchA) can also be involved in supplying the lateral thalamus; however, the question of its contribution to vascular supply is still controversial [4][5][6]. Four main vascular territories are differentiated on the basis of the most important infarct patterns: the anterolateral, the inferomedial, the inferolateral, and the posterolateral regions of supply ( Figure 3a).…”
Section: Vascular Supply Of the Thalamusmentioning
confidence: 99%
“…The medial posterior choroidal arteries consist of one to two blood vessels originating from the distal P1 or the proximal P2 segment. The posterior lateral choroidal arteries can number up to six and originate from the distal P2 or the proximal P3 segments of the PCA [4][5][6].…”
Section: Vascular Supply Of the Thalamusmentioning
confidence: 99%
“…Even considering that spatial resolution is not optimal to detect very small ischemic lesions and possible susceptibility effects in the posterior fossa, there is still a lack of DSC studies of the posterior circulation. & Weidauer et al [16] used DSC perfusion MRI for a more detailed characterization of paramedian thalamic infarction and were able to demonstrate a hypoperfusion in the PCA territory due to occlusion or severe stenosis of the distal basilar artery and/or the P1-segments of the PCA. & In a more recent prospective study, we demonstrated the feasibility and value of DSC perfusion MRI in acute pontine stroke [17••].…”
Section: Diffusion-weighted and Diffusion Tensor Imagingmentioning
confidence: 99%